Sinkronisasi Regulasi Teknologi Informasi dengan Hukum Pidana Nasional: Harmonisasi Norma dan Penyelesaian Konflik Yurisdiksi di Era Digital - Gilang Rizki Aji Putra (UIN Jakarta, 2021)
Information technology regulation in Indonesia, particularly the Electronic Information and Transactions Law, has developed sectorally and often lacks alignment with the national criminal law framework. This article analyzes the level of synchronization, identifies inconsistencies, and proposes an integrative harmonization approach. Using normative legal research with statutory, conceptual, and comparative approaches, the study finds horizontal disharmony between the ITE Law, the Criminal Code, and related laws. This condition creates legal uncertainty, overlapping offenses, and inconsistent enforcement. Integrated legislative reform and clearer conflict-of-norm guidelines are necessary. Keywords: Regulatory Synchronization, Criminal Law, ITE Law, Norm Harmonization, Lex Specialis